Factors influencing the occurrence of airway hyperreactivity in the general population: the importance of atopy and airway calibre. - Britton, J; Pavord, I; Richards, K; Knox, A; Wisniewski, A; Wahedna, I; Kinnear, W; Tattersfield, A; Weiss, S (1994)
The factors that determine the occurrence of airway hyperreactivity in the general population are not clearly understood. This study was designed to assess the independent effects of age, atopy, smoking and airway calibre. In a random sample of 2,415 adults aged 18-70 yrs we measured reactivity to methacholine as the dose provoking a 20% fall (PD20) in one-second forced expiratory volume (FEV1), atopy as the mean skin wheal response to three common environmental allergens, and airway calibre as the baseline FEV1 in absolute terms, as percent predicted (FEV1 % predicted) and as percent forced vital capacity (FEV1 % FVC). Hyperreactivity, defined as a PD20 < or = 12.25 mumol, was present in 314 (13%) of the sample, and before adjustment for FEV1 was more common in females (independent odds ratio (OR) = 2.05 (95% confidence interval 1.6-2.7)), current smokers (OR = 1.89 (1.3-2.6)), atopics (OR = 1.39 (1.3-1.5) per mm skin wheal), and in older age groups (OR for age 60-70 yrs relative to 18-29 yrs = 2.70 (1.7-4.3)). However, the odds of hyperreactivity were also strongly and independently related to absolute FEV1 (OR = 0.46 (0.27-0.77) per litre), FEV1 % predicted (OR = 0.96 (0.94-0.98) per percent), and FEV1 % FVC (OR = 0.92 (0.90-0.94) per percent; combined chi-square on 3 df = 312, p << 0.0001).(ABSTRACT TRUNCATED AT 250 WORDS)